Research on Inflatable Fire Isolation Belt Based on Multi steady State Compression Torsion Composite Energy Absorbing Structure - Fu, Shengwen; Sun, Zhongyu; Ren, Guohui; Xu, Hao; Li, Rongyu; Shang, Shengchang (Transactions on Environment, Energy and Earth Sciences, 2024)
Reducing complications and preventing forest fires is the core of forest fire management When a forest fire occurs, it is of great significance to control forest fires by reason of setting up fire isolation zones In this paper, an unstable firehouse isolation belt based on multiple pressure force composite energy absorbing structure is proposed, and the high heat resistance, high performance and capability of the scheme are verified by simulation experiments The airport part of the fire isolation belt options a dot matrix energy absorbing structure molded by base fiber and resin pre, which uses the pressure difference generated by the temperature difference for rapid impact, and the box uses the hole design to realize the flexible storage of the airport, and crosses and fixes the main part through a new type of ground nail and aramid drop e to divide the forest into small blocks, and can separate the fire area without breaking the ring trees The overall operation is simple, the device is flexible and portable, and can be reused, compared with the traditional fire isolation belt, this device greatly improves the fire prevention efficiency and reduces the fire loss.